Video Development to Increase Coverage of Exclusive Breastfeeding Promotion in Aceh Province, Indonesia - Anita, Anita; Ramli, Nurlaili (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The percentage of exclusive breastfeeding for infants 0–6 months in Aceh in 2019 was 55.24% and decreased compared to 2018, 60.84%. Exclusive breastfeeding in Aceh Province is still below the national figure. One of the efforts to increase the coverage of exclusive breastfeeding is the development of videos. The messages in the videos most influence the perception of who is breastfeeding. AIM: The aim of the study is video development to increase coverage of exclusive breastfeeding in Aceh Province, Indonesia. METHODS: This study uses the research and development research method. The research was conducted in the Darul Imarah district. The research subjects in this development research were breastfeeding mothers. Data collection was carried out using assessment sheets, observations, questionnaire sheets, process skills test sheets carried out by compiling tests/assessment instruments, selecting media, selecting formats, and preparing preliminary designs/designs. The development stage is carried out by expert validation and development trials. RESULTS: The results showed that researchers’ dissemination and implementation to breastfeeding mothers showed that 70% of babies received exclusive breastfeeding one month after seeing the video, and there were still 40% of babies who had received formula milk. The expert team’s assessment results showed that 73.3% still needed to match the Acehnese language with the players’ scenario. Overall, POMA video development effectively increases exclusive breastfeeding in Darul Imarah District, Aceh Besar District. The message presented in the video Poma Harapan can give confidence to the audience that exclusive breastfeeding coverage. CONCLUSION: POMA video development is effective in increasing exclusive breastfeeding in Darul Imarah District, Aceh Besar District.